Ultraviolet B Inhibits IL-17A/TNF-α-Stimulated Activation of Human Dermal Fibroblasts by Decreasing the Expression of IL-17RA and IL-17RC on Fibroblasts - Yin, Li; Hu, YingYing; Xu, JiaLi; Guo, Jing; Tu, Jie; Yin, ZhiQiang (Frontiers in Immunology, 2017)
Background: Psoriasis is a chronic immune-mediated inflammatory disease and a mixed Th1/Th17 cytokine environment plays a critical role in the pathogenesis of psoriasis. Dermal fibroblasts secrete certain cytokines such as IL-6, IL-8 and CXCL-1, contributing to the hyperproliferative state of the epidermis in psoriatic skin. UVB phototherapy is one of the most commonly used treatments in psoriasis but the influence of Ultraviolet B (UVB) on human dermal fibroblasts (HDFs) in psoriasis treatment is not completely understood. Objectives: We conducted this study to mimic a psoriatic microenvironment in order to investigate and illustrate the combined effects of UVB, IL-17A and TNF-α on HDFs. Methods: The cultured HDFs were obtained from foreskin samples and divided into four groups, as follows: Control; IL-17A/TNF-α; UVB; and IL-17A/TNF-α + UVB. Cultured HDFs were irradiated with 30 mJ/cm2 UVB followed by addition of IL-17A/TNF-α and incubated for 24 hours. We used Real-time quantitative PCR, Western blot, ELISA analysis and Flow cytometry to examine gene and protein expression of related pro-inflammatory cytokines and chemokines and receptors. Results: HDFs produced significant IL-6, IL-8 and CXCL-1 in response to IL-17A/TNF-α stimulation and UVB irradiation but UVB irradiation inhibited IL-17A/TNF-α-induced IL-6, IL-8 and CXCL-1 expression and down-regulated the expression of IL-17RA and IL-17RC at both gene and protein levels. Additionally, UVB irradiation induced significant TGF-β1 protein secretion and expression of Smad3 mRNA and protein by HDFs. TGF-β1 significantly induced the expression of Smad3 mRNA and down-regulated the IL-17RA and IL-17RC expression on HDFs. Conclusion: UVB irradiation inhibits IL-17A/TNF-α-induced IL-6, IL-8 and CXCL-1 production in HDFs by decreasing the expression of IL-17RA and IL-17RC on fibroblasts through TGF-β1/Smad3 signaling pathway, which reveals a new mechanism of the therapeutic action of UVB on psoriasis.